The fear factor: Xenoglossophobia or how to overcome the anxiety of speaking foreign languages - Heiner Böttger; Deborah Költzsch (Peoples' Friendship University of Russia (RUDN University), 2020)
The article approaches a ubiquitous as well as a rarely adequately addressed problem area of learning and teaching foreign languages. It concentrates on xenoglossophobia, the fear of speaking foreign languages. Why do avoidance strategies as well as phobias develop during childhood especially in the foreign language classroom whenever it comes to the productive usage of the English language? Psychological, pedagogical, didactical as well as language related and neuroscientific findings are analysed and interpreted in order to help answer central questions like the above. The theoretical indications are further supported by a fundamental pilot study based on the productive language usage of foreign language students (n=108) and the according reflective and prospective analysis. The second part of the article brings all these findings together and outlines language didactical, meaningful, positive preventive, diagnostical, and therapeutic opportunities for intervention in the foreign language classroom.